DIPG-01. TARGETING THE POLYAMINE PATHWAY AS A NOVEL THERAPEUTIC TREATMENT AGAINST DIFFUSE INTRINSIC PONTINE GLIOMA. Issue 2 (22nd June 2018) - Khan, Aaminah; Gamble, Laura; Yu, Denise; Joshi, Swapna; Franshaw, Laura; Burns, Mark; Norris, Murray; Haber, Michelle; Tsoli, Maria; Ziegler, David
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive paediatric brainstem tumour, with a median survival below 1 year. Polyamines, frequently upregulated in cancer, are small intracellular polycations that control key biological processes including cell replication, translation and differentiation. The aim of this study was to investigate the efficacy of polyamine pathway inhibitors as a therapeutic strategy against DIPG. Difluoromethylornithine (DFMO) is an FDA-approved inhibitor of the enzyme ornithine decarboxylase (ODC1), a key driver of polyamine synthesis. By qPCR and western blotting, high expression levels of key players of the polyamine pathway were observed in a panel of DIPG samples. Using cytotoxicity and soft-agar clonogenic assays, we found that DFMO inhibited the proliferation of DIPG neurospheres. Treatment with the novel polyamine transport inhibitor, AMXT-1501 led to reduced uptake of the radiolabelled polyamine, spermidine, confirming polyamine transport inhibition in DIPG cells. Addition of AMXT-1501 to DFMO showed a potent and synergistic inhibition of DIPG neurosphere proliferation. Western blotting and flow cytometry analysis of Annexin V-stained cells showed that treatment with DFMO or AMXT-1501, alone or in combination, led to apoptotic induction. Consistent with the in vitro results, the combination of DFMO and AMXT-1501 significantly prolonged the survival of all mice bearing DIPG orthografts with 6/9 mice surviving until the humane endpoint of 160 days, representing the most effective combination treatment we have tested to date in our highly aggressive DIPG animal model. AMXT-1501 is currently in clinical development and following completion of adult Phase 1 studies, a clinical trial for DIPG patients is planned.